THE FORMATION AND PHILOSOPHICAL DESCRIPTION OF THE THINKERS OF THE TIMURI PERIOD AND THEIR SOCIAL AND ETHICAL APPROACHES (Scientific journal of the Fergana State University, 2024)
In the article, the theoretical-methodological foundations of researching the socio-ethical views of the thinkers of the Timurid era, the hermeneutic bases of their socio-ethical views, the educational significance of the socio-ethical views of the thinkers of the Timurid era in New Uzbekistan are studied. The formation of thinkers of the Timurid period and their socio-ethical views was also analyzed.